Confirmation and Control of Imazamox-Resistant Shattercane - V. Kumar; R. Liu; T. L. Lambert; R. Perumal; B. Bean (Kansas Agricultural Experiment Station Research Reports, 2022)
Shattercane is a summer annual grass weed species commonly found in grain sorghum producing regions, including Kansas. Recent development and commercialization of grain sorghum hybrids with tolerance to acetolactate synthase (ALS) and acetyl-CoA-carboxylase (ACCase) inhibiting herbicides will allow producers to use these herbicides for in-season control of shattercane. In a recent field survey, three shattercane populations (DC8, GH4, and PL8) collected from sorghum fields in northwestern Kansas survived the field-use rate (6 fl oz/a) of postemergence (POST) applied IMIFLEX (imazamox). The main objectives of this research were to (1) confirm and characterize the level of resistance to imazamox in those suspected imazamox-resistant (IMI-R) shattercane populations, and (2) determine the effectiveness of alter-native POST herbicides for controlling IMI-R shattercane populations. Imazamox dose-response experiments were conducted in greenhouse conditions at the Kansas State University Agricultural Research Center near Hays, KS. A susceptible shattercane population (SUS) collected from sorghum field in Rooks County, KS, was included for comparison. Dose-response analysis revealed that all three populations exhibited a 3.5- to 5.3-fold resistance to imazamox as compared to SUS population. In a field study, POST treatments of nicosulfuron (Zest), quizalofop (Aggressor), clethodim (Select Max), glyphosate (Roundup PowerMax), and glufosinate (Liberty) provided an excellent control (92 to 100%) of IMI-R population at 21 days after treatment (DAT). These results report the first case of imazamox-resistant shattercane in Kansas. Growers should adopt effective alternative POST herbicides tested in this research for managing IMI-R shattercane.
Keywords: Dose-response; imazamox; resistance; shattercane